Exploring spoken English - Carter, Ronald (Cambridge Univ. Press, 2001)
Exploring Spoken English is a practical guide to the features of natural spoken English, designed for teachers and advanced learners of English for use in groups and for self-study. The material consists of 20 varied extracts of authentic spoken English drawn from the Cambridge University Press and University of Nottingham corpus of spoken English. All the extracts are on an accompanying cassette. Each unit contains an activity for the reader and a line-by-line commentary offering new insights into grammar, vocabulary and discourse patterns in the text. The accompanying cassette contains all the extracts, some re-recorded for the purposes of clarity.